Pathobiology of pulmonary arterial hypertension and right ventricular failure - Voelkel, Norbert F. (2012)
Pulmonary arterial hypertension (PAH) is no longer an orphan disease. There are three different classes of drugs for the treatment of PAH that are currently being used and an increasing number of patients are being treated with a single drug or combination therapy. During the last 25 yrs, new insights into the pathobiology of PAH have been gained. The classical mechanical concepts of pressure, flow, shear stress, right ventricle wall stress and impedance have been complemented with the new concepts of cell injury and repair and interactions of complex multicellular systems. Integrating these concepts will become critical as we design new medical therapies in order to change the prognosis of patients with these fatal diseases. This review intends to summarise recent pathobiological concepts of PAH and right ventricle failure mainly derived from human studies, which reflect the progress made in the understanding of this complex group of pulmonary vascular diseases.